Response to "Comment on Khanna (2023)" - Gaurav Khanna (Institute for Replication (I4R), 2023)
Roodman (2023) (henceforth R23) re-evaluates Khanna (2023) (henceforth K23). R23 is able to replicate K23's results, highlighting no mistakes in K23's analysis. R23 argues that K23's results may be sensitive to recreating part of the underlying district-level sample, using a subset of K23's datasets. In this reply, I show that despite concerns with R23's sample construction, K23's results are robust to evaluating R23's sample as given. R23 raises other secondary questions, which this reply answers. I also address R23's misinterpretations of K23's general equilibrium model.
Additional information: This paper responds to: Roodman, David. 2023. Large-Scale Education Reform in General Equilibrium: Regression Discontinuity Evidence from India - Comment. I4R Discussion Paper Series No. 70. Institute for Replication. https://hdl.handle.net/10419/276969
Keywords: 330